Prevalence and factors associated with antenatal care utilization in Ethiopia: an evidence from demographic health survey 2016 - Berhan Tsegaye; Mohammed Ayalew (BMC, 2020)
Abstract Background Ethiopia is one of the sub-Saharan African country with high maternal mortality ratio (MMR). According to Ethiopian demographic health survey (EDHS) 2016 report, MMR is 420 among 100,000 live births. Antenatal care utilization is a key intervention to reduce these deaths through problem detection and treatment, promotion of health seeking behavior, and preparing pregnant women for birth. Therefore, this study aimed to assess prevalence and factors associated with antenatal care service utilization in Ethiopia in 2016. Methods Secondary data analysis was done on EDHS 2016. It was a stratified, two-stage, and cluster sampling design. Analysis has been restricted to antenatal care utilization among women who delivered at least one time in the past five years. Data were weighted to correct sampling bias. Moreover, complex data analysis was done. Bi-variate and multivariable logistic regression analyses were carried out. Adjusted odds ratio with 95% confidence interval was computed and P-value less than 0.05 considered as a statistically significance level for identification of association. Results Prevalence of antenatal care utilization was 62.8% [95%CI: 60.9, 64.6] in this study. Maternal educational status of primary school (AOR = 1.8,95%CI:1.2, 2.6), maternal educational status of secondary school (AOR = 4.4,95%CI: 1.1, 17.3), women who listen radio less than 1 per week (AOR = 1.9,95%CI:1.12,3.34), women who listen radio at least 1 per week (AOR = 2.6,95%CI:1.4,4.8), women in rich wealth quintile (AOR = 1.9,95%CI: 1.1, 3.2) were factors positively associated with antenatal care utilization. However, women who had traditional belief (AOR = 0.1,95%CI:0.02,0.49), and women who had five children and above (AOR = 0.6,95%CI: 0.3, 0.9) were factors associated negatively with antenatal care utilization. Conclusions Prevalence of antenatal care utilization is still low in Ethiopia in 2016. Maternal higher maternal educational status, frequent radio listening, higher wealth quintile, traditional belief, and greater number of children were found to be associated significantly with antenatal care utilization. Consequently, socio-economic status should be enhanced, information should be accessed by women about antenatal care utilization and family planning service through mass media. Furthermore, intensive community education program should be designed for traditional believers to increase uptake of antenatal care by stakeholders.